Prevalence of people who could benefit from augmentative and alternative communication (AAC) in the UK: determining the need. Issue 6 (26th April 2016) - Creer, Sarah; Enderby, Pamela; Judge, Simon; John, Alex
Abstract: Background: Commissioners and providers require information relating to the number of people requiring a service in order to ensure provision is appropriate and equitable for the population they serve. There is little epidemiological evidence available regarding the prevalence of people who could benefit from augmentative and alternative communication (AAC) in the UK. Aim: To determine the prevalence of people who could benefit from AAC in the UK. Methods & Procedures: An epidemiological approach was taken to create a new estimate of need: the prevalence of the main medical conditions and specific symptoms leading to the requirement for AAC were identified from the literature and AAC specialists were consulted to estimate the number of people who may require AAC. Outcomes & Results: A total of 97.8% of the total number of people who could benefit from AAC have nine medical conditions: dementia, Parkinson's disease, autism, learning disability, stroke, cerebral palsy, head injury, multiple sclerosis and motor neurone disease. The total expectation is that 536 people per 100 000 of the UK population (approximately 0.5%) could benefit from AAC. Conclusions & Implications: To provide accurate figures on the potential need for and use of AAC, data need to be consistently and accurately recorded and regularly reviewed at a community level. The existing data suggest an urgent need for more accurate and up to date information to be captured about the need for AAC in the UK to provide better services and ensure access to AAC strategies, equipment and support.